Optimization of mango herbal Quarg type cheese with mango pulp and spices - Ramteke, Sachin P; Kankhare, Dhiraj H; Dhumal, Vishal S; Desale, Rahul J; Patil, Vishal P (Indian Journal of Dairy Science, 2020)
The present study was carried out to optimize the levels of mango pulp and spices in quarg type cheese to prepare mango herbal Quarg type cheese. The sensory evaluation was carried out in respect of flavour, body and texture, colour and appearance and overall acceptability. The different level of mango pulp, cardamom and clove were studied in preliminary trials and five treatments were taken for experimental studies. Level selected for mango pulp was 27 per cent and levels of cardamom (0.6% and 0.7%) and clove (0.4% and 0.5%) were finalized for further study. The treatment T2 (27 per cent mango pulp + 0.6 per cent cardamom + 0.4 per cent clove) was rated superior among all experimental treatments.Â